Maternal uterine NK cell–activating receptor KIR2DS1 enhances placentation - Xiong, Shiqiu (J Clin Invest, 2013)
Reduced trophoblast invasion and vascular conversion in decidua are thought to be the primary defect of common pregnancy disorders including preeclampsia and fetal growth restriction. Genetic studies suggest these conditions are linked to combinations of polymorphic killer cell Ig-like receptor (KIR) genes expressed by maternal decidual NK cells (dNK) and HLA-C genes expressed by fetal trophoblast. Inhibitory KIR2DL1 and activating KIR2DS1 both bind HLA-C2, but confer increased risk or protection from pregnancy disorders, respectively. The mechanisms underlying these genetic associations with opposing outcomes are unknown. We show that KIR2DS1 is highly expressed in dNK, stimulating strong activation of KIR2DS1(+) dNK. We used microarrays to identify additional responses triggered by binding of KIR2DS1 or KIR2DL1 to HLA-C2 and found different responses in dNK coexpressing KIR2DS1 with KIR2DL1 compared with dNK only expressing KIR2DL1. Activation of KIR2DS1(+) dNK by HLA-C2 stimulated production of soluble products including GM-CSF, detected by intracellular FACS and ELISA. We demonstrated that GM-CSF enhanced migration of primary trophoblast and JEG-3 trophoblast cells in vitro. These findings provide a molecular mechanism explaining how recognition of HLA class I molecules on fetal trophoblast by an activating KIR on maternal dNK may be beneficial for placentation.